PRODUKSI BIOGAS DARI LIMBAH KOTORAN SAPI PERAH DENGAN REAKTOR BIOGAS SISTEM BATCH DI DESA LEREP KABUPATEN UNGARAN - Didik Wisnu Widjajanto; Heny Kusumayanti; Sri Rejeki (Universitas Diponegoro, 2021)
Abstract Biogas is mixed gas of methane(CH4), carbondioxide (CO2) and others which is produced as a result of moterial degradation of organic material such as animal and humon feces or plant byproduct by methanagen bacterial activity in biodigester. The present work is aimed to produce biogas fromfeces of milk cow. Biogas reactor used is built by IbM team of